Social Interaction and Public Service: The Role of Social Dynamics in Service Quality - Sigit Wahyudi; Muhammad Aulia Rofi Alhasani; Iwan Satibi; Sri Suwartiningsih; Achmad Fathor Rosyid (Jurusan Administrasi Publik FISIP UIN SGD Bandung, 2023)
This article investigates the role of social dynamics in influencing the quality of public services through analysis of social interactions between public service providers and the community. Through surveys covering various social, demographic, and geographic groups in Indonesia, research findings reveal that positive and responsive social interactions can significantly influence people's perceptions of the quality of public services. Apart from that, community participation in decision-making regarding public services also emerged as an important factor. Social and demographic factors such as age, education, gender, and location of residence also play a role in shaping these perceptions. The results of these findings include the importance of improving communication skills training of public service officers, supporting community participation, and designing responsive policies. This article advocates for a more holistic approach to improving the quality of public services by taking into account various social dynamic factors.